Magnetic Field Sensing: Printing 1D Assembly Array of Single Particle Resolution for Magnetosensing (Small 19/2018). Issue 19 (9th May 2018) - Gao, Meng; Kuang, Minxuan; Li, Lihong; Liu, Meijin; Wang, Libin; Song, Yanlin
Abstract : In article number1800117, Lihong Li, Yanlin Song, and co‐workers prepare a 1D assembly array of single particle resolution inspired by the magnetosome structure via an inkjet printing method under magnetic guiding. In the confined printed droplet, particles are attracted "tip‐to‐tip" into 1D assembly, which pins on the substrate with a low receding angle. The 1D array can be used for magnetic field sensing, electronic devices, biosensing and biometric techniques.